The Effectiveness of Hyperbaric Oxygen Treatment in Patients with Complex Regional Pain Syndrome: A Retrospective Case series - Hájek, Michal; Chmelař, Dittmar; Tlapák, Jakub; Klugar, Miloslav (International journal of medical sciences, 2024)
Background: Complex regional pain syndrome (CRPS) presents as persistent regional pain, both spontaneous and triggered. The demand persists for innovative treatments that patients can endure with minimal adverse effects. Hyperbaric oxygen therapy (HBOT) emerges as a possible intervention in this regard. Methods: The main objective of this work is to retrospectively analyse a case series of patients diagnosed with CRPS treated in the Centre of Hyperbaric Medicine Ostrava over two years (period 2018-2019). The HBOT was applied at 2.0-2.4 absolute atmosphere (ATA) once a day. Results: A total of 83 patients with CRPS were treated with HBOT. 98% of cases reported pain, 92% reported limitation of movement of the affected limb, 87% had swelling of the limb, 41% had lividity and 70% had sensory problems. The mean number of HBOT exposures was 22.0 ± 7.1. At the end of HBOT treatment, 86% of cases had symptoms relief. The mean VAS value of pain at rest before the start of HBOT was 3.2±3.0, after treatment it was 1.6±1.9 (p<0.001). In a pain at activity it was 6.1±2.4 and 3.7±2.4 (p<0.001), respectively, at the end of HBOT. The value of the functional assessment of the limb was 7.0±2.0 and 4.3±2.4 (p<0.001), respectively, at the end of treatment. 79 cases were included in the end-of-treatment assessment. 23 cases (29%) were evaluated as large clinically significant response, 48 cases (61%) were evaluated as partial response with minimally important difference. The results showed larger clinical HBOT effect in cases of disease duration up to 3 and 6 months (p=0.029). Conclusions: The majority of patients improved pain and functional state of the affected limb. Our data also suggests the sooner after diagnosis of CRPS is HBOT started, the treatment has larger clinical effect. There was no serious HBOT-related complication or injury.
Keywords: case series; visual analog scale; Pain Measurement; Humans; lidé středního věku; komplexní regionální syndromy bolesti; Female; Aged; dospělí; výsledek terapie; hyperbaric oxygen therapy; senioři; lidé; pain; Adult; ženské pohlaví; complex regional pain syndrome; Male; Middle Aged; Retrospective Studies; hyperbarická oxygenace; Treatment Outcome; Complex Regional Pain Syndromes; retrospektivní studie; Hyperbaric Oxygenation; mužské pohlaví; měření bolesti